1992
DOI: 10.1002/mcs.1220040407
|View full text |Cite
|
Sign up to set email alerts
|

Programmed‐temperature injector for large‐volume sample introduction in capillary gas chromatography and for liquid chromatography‐gas chromatography interfacing

Abstract: The introduction of large sample volumes in capillary gas chromatography is becoming increasingly important in various application areas. Especially in the analysis of very dilute sample (e.g., environmental samples) and in coupled LC‐GC, large volume sampling is extremely important. Programmed‐temperature sample introduction is shown to be an attractive technique for these purposes. In this paper we present some applications of large volume sampling in environmental analysis. Water samples were analyzed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The introduction of large volumes with the use of such an injector in solvent-split mode was first investigated in the 1970s. Staniewski, Cramers and co-workers (12)(13)(14)(15)(16)(17) demonstrated that by reducing the injector temperature and by increasing the purge gas during the solvent elimination it was easier to remove solvent, and showed that by using chambers packed with porous glass beads instead of Tenax TA or Thermotrap recovery of solutes may be improved.…”
Section: Vaporization With Hot Injectorsmentioning
confidence: 99%
“…The introduction of large volumes with the use of such an injector in solvent-split mode was first investigated in the 1970s. Staniewski, Cramers and co-workers (12)(13)(14)(15)(16)(17) demonstrated that by reducing the injector temperature and by increasing the purge gas during the solvent elimination it was easier to remove solvent, and showed that by using chambers packed with porous glass beads instead of Tenax TA or Thermotrap recovery of solutes may be improved.…”
Section: Vaporization With Hot Injectorsmentioning
confidence: 99%
“…[9] or by off-line or on-line extraction coupled to gas chromatography [10]; the latter technique was applied to the determination of PAHs and herbicides in water samples.…”
Section: Figurementioning
confidence: 99%
“…Different approaches are available for achieving largevolume injection in capillary gas chromatography: oncolumn injection [1][2][3][4][5][6], programmed-temperaturevaporization injection [7][8][9][10] or splitless injection with solvent diversion [11,12]. Although the use of largevolume injection in GC has been described in several papers, few references deal with the determination of pesticides in environmental samples.…”
Section: Introductionmentioning
confidence: 99%
“…The elimination of the solvent and the gas chromatographic analysis of the thermally desorbed compounds is subsequently performed. Specifically, the optimisation of a number of variables involved in the retention of the target solutes in an adsorbent kept inside the PTV injector body has allowed the determination of trace compounds in very different matrices (Mol, Janssen, Cramers, Vreuls, & Brinkman, 1995;Staniewski, Janssen, Cramers, & Rijks, 1992;Villén, Señoráns, Reglero, & Herraiz, 1995, 1996.…”
Section: Introductionmentioning
confidence: 99%